Tinjauan Faktor Air dan Sanitasi dengan Kejadian Stunting pada Balita - Mardiyatun Nasyidah; Nur Alam Fajar; Najmah Najmah (Jurnal Kesehatan Komunitas, 2022)
Globally, malnutrition manifests most frequently as a failure to achieve linear growth. Stunting occurs when a person's growth is restricted. Stunting is a major public health concern because it affects an estimated 165 million children younger than 5 years old, and the primary goal is to reduce stunting prevalence by 40% between 2010 and 2025. Stunting is linked to both water and environmental issues as well as nutritional ones. sanitation. The purpose of this literature review is to investigate the connection between the availability of clean water and the rate of stunting in children younger than five. Google Scholar, PlosOne, SpringerLink, the Wiley Online Library, and PubMed are just some of the electronic databases used in this literature review/narrative review/method of research. "water + sanitation + child + stunting" are the search terms used to uncover this article's foundation. Articles that explain the connections between poor water and sanitation and stunting in children younger than five and were published between 2015 and 2021 were considered for inclusion. A review of 20 articles found that access to clean water and sanitation services (such as the availability of toilets, the frequency with which people defecate in the open, and the method by which they dispose of their toddlers' waste) were all linked to reduced height and weight in children under five. Researchers found that access to clean water and toilets were both risk factors for stunting in children younger than five. Stunting can be avoided with more health awareness campaigns and cross-sector collaboration on nutrition interventions.